2017
DOI: 10.1021/acs.langmuir.7b02060
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptides Embedded in a Lipid Bilayer Membrane as Synthetic Water Channels

Abstract: Water channels are essential to life sciences and many biological processes. We report a molecular simulation study on dipeptides embedded in a lipid (dipalmitoylphosphatidylcholine) membrane as synthetic water channels. Five dipeptides are examined including FF, FL, LF, and LL (with hydrophilic channels) and AV (with hydrophobic channel). It is found that AV is unstable in the lipid membrane due to incompatible interaction between the hydrophilic external surface of AV and the hydrophobic lipid tails; whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Altogether, these site-specific peptide probes enabled us to view water penetration into the hydrophobic region of the bilayer, which may be otherwise thermodynamically unfavorable in peptide-free bilayers. Previous literature has observed negligible water presence beyond the ester carbonyl in pure lipid membranes (75)(76)(77) and has also suggested that embedded amino acids and peptides may facilitate water diffusion across lipid bilayers and into the alkyl bulk (6,(78)(79)(80)(81)(82). Our results are consistent with this literature; however, additional methods beyond the scope of this study are required to rule out potential peptide multimers in the membrane.…”
Section: Discussionsupporting
confidence: 91%
“…Altogether, these site-specific peptide probes enabled us to view water penetration into the hydrophobic region of the bilayer, which may be otherwise thermodynamically unfavorable in peptide-free bilayers. Previous literature has observed negligible water presence beyond the ester carbonyl in pure lipid membranes (75)(76)(77) and has also suggested that embedded amino acids and peptides may facilitate water diffusion across lipid bilayers and into the alkyl bulk (6,(78)(79)(80)(81)(82). Our results are consistent with this literature; however, additional methods beyond the scope of this study are required to rule out potential peptide multimers in the membrane.…”
Section: Discussionsupporting
confidence: 91%
“…Our results could possibly explain the earlier stages of water permeability findings of antimicrobial peptides that favor water penetration in bacterial membranes even at very low peptide concentrations, without destroying the membrane integrity. 92–95 However, simulations with higher peptide concentrations and larger membranes should be performed to confirm the positive correlation between peptide concentration and water flow and concentration within membranes.…”
Section: Discussionmentioning
confidence: 99%
“…116 Another study has also hypothesized that the permeability of biomimetic dipeptide channels can be affected by the lateral stress and strain forces on the lipid membrane. 117 It is obvious that the assimilation of water channels into membranes can induce structural changes in the lipid bilayer and the consequential water transport pathway through the latter. We recommend future studies to resolve the intricate interplay between channels and the lipid bilayer because the permselectivity of such unique membrane designs remains to be resolved by experimental studies.…”
Section: Different Membrane Designsmentioning
confidence: 99%